2017
DOI: 10.3892/ol.2017.7609
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic acid B suppresses cell proliferation and induces apoptosis in osteosarcoma through p38-mediated reactive oxygen species generation

Abstract: Abstract. The present study aimed to investigate the potential anticancer effect and mechanisms of salvianolic acid B on osteosarcoma. Salvianolic acid B suppressed osteosarcoma cell proliferation and induced apoptosis in the osteosarcoma MG63 cell line, and activated the expressions of cleaved caspase-3, phosphorylated-tumor protein (p)38 mitogen-activated protein kinase (p-p38 MAPK) and phosphorylated-p53 (p-p53) proteins in the MG63 cells. Additionally, Salvianolic acid B also increased the level of reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…www.science.org/doi/10.1126/scitranslmed.abb3312 Materials and Methods Figs. S1 to S10 Tables S1 to S3 Data file S1 References (56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67) View/request a protocol for this paper from Bio-protocol.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…www.science.org/doi/10.1126/scitranslmed.abb3312 Materials and Methods Figs. S1 to S10 Tables S1 to S3 Data file S1 References (56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67) View/request a protocol for this paper from Bio-protocol.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…For cancer cells, Sal B has the opposite effect on regulating cell apoptosis. Previous studies in vitro have shown that Sal B can not only inhibit the proliferation and induce apoptosis of osteosarcoma cells by promoting the p38-MAPK pathway to mediate ROS production (Zeng et al, 2018), but also promote the autophagy of colorectal cancer cells and hepatocellular carcinoma cells by inhibiting the Akt/mTOR signaling pathway (Gong et al, 2016;Jing et al, 2016). Since mitochondria are both the main source of ROS and the site of cellular energy metabolism, cell types with abnormal energy metabolism such as cancer cells may have higher levels of ROS to maintain a high proliferation rate.…”
Section: Inhibit Cancer Cells Proliferation and Metastasis In Vitromentioning
confidence: 99%
“…Therefore, the anti-inflammatory effect of Sal B may be mediated by its regulation of Nrf2/Keap1. Several studies have shown that Sal B can inhibit the expressions of TNF-α, IL-1β, IL-6 and other pro-inflammatory factors in a variety of diseases to exert a good anti-inflammatory effect, and its mechanisms mainly involve the TNF-α/NF-κB signaling pathway and TLR pathway ( Zeng et al, 2015 ; Zhang et al, 2015 ; Xu et al, 2017 ) ( Table 1 ; Figure 5 ). Most studies involve the protective effect of Sal B in neuroinflammation, and middle cerebral artery occlusion (MCAO) is obviously a commonly used model for rat brain I/R injury, which may be more suitable for the pathological state of human cerebral ischemia.…”
Section: Pharmacological Mechanisms Of Salvianolic Acid B Based On Anmentioning
confidence: 99%
“…Previous studies have suggested that mitigating ROS production by administration of antioxidants such as vitamin C following ROSC was able to reduce myocardial injury, resulting in improved postresuscitation myocardial function [43,44]. Because oxidative stress is causatively [48][49][50]. Thus, the role of Sal B in inhibiting or promoting oxidative stress may be dependent on cell and tissue type.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of Sal B in regulating oxidative stress has been reported in several cell types; interestingly, Sal B had antioxidant effects in several cell types, but oxidative effects in others. For example, Sal B inhibited oxidative stress in endothelial cells, smooth muscle cells, and Schwann cells [ 45 47 ], but facilitated oxidative stress in some tumor cells, such as glioma, osteosarcoma, and colorectal carcinomas [ 48 50 ]. Thus, the role of Sal B in inhibiting or promoting oxidative stress may be dependent on cell and tissue type.…”
Section: Discussionmentioning
confidence: 99%